2010
DOI: 10.1186/1423-0127-17-78
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in hippocampal serotonergic and INSR function in streptozotocin induced diabetic rats exposed to stress: neuroprotective role of pyridoxine and Aegle marmelose

Abstract: Diabetes and stress stimulate hippocampal 5-HT synthesis, metabolism and release. The present study was carried out to find the effects of insulin, Aegle marmelose alone and in combination with pyridoxine on the hippocampal 5-HT, 5-HT2A receptor subtype, gene expression studies on 5-HT2A, 5-HTT, INSR, immunohistochemical studies and elevated plus maze in streptozotocin induced diabetic rats. 5-HT content showed a significant decrease (p < 0.001) and a significant increase (p < 0.001) in 5-HIAA in hippocampus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 46 publications
1
10
0
2
Order By: Relevance
“…These results are in agreement with other reports using animal models of type 1 and type 2 diabetes and different anxiety tests such as the open field, elevated plus maze, hole-board, and social interaction tests (Ramanathan et al, 1998;Kamei et al, 2001;Abraham et al, 2010;Husain et al, 2011). Although blood glucose levels were already increased 5 days after the STZ injection, the anxiogenic-like response was observed 15 days after its administration.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results are in agreement with other reports using animal models of type 1 and type 2 diabetes and different anxiety tests such as the open field, elevated plus maze, hole-board, and social interaction tests (Ramanathan et al, 1998;Kamei et al, 2001;Abraham et al, 2010;Husain et al, 2011). Although blood glucose levels were already increased 5 days after the STZ injection, the anxiogenic-like response was observed 15 days after its administration.…”
Section: Discussionsupporting
confidence: 95%
“…Grigsby et al (2002) reported that 14% of patients with type 1 or type 2 diabetes presented with generalized anxiety disorder, 27% had other anxiety disorder (not specified), and 40% showed elevated anxiety symptoms. Similar to these findings, preclinical studies report that rodents with streptozotocin (STZ)-induced diabetes show anxiogeniclike behavior in different anxiety paradigms (Ramanathan et al, 1998;Kamei et al, 2001;Abraham et al, 2010).…”
Section: Introductionmentioning
confidence: 69%
“…We observed signi cant reduction in fasting insulin and HOMA-IR. In some studies, it has also been shown to decrease fasting blood glucose (13,22) and insulin resistance (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant (20) and antiin ammatory (15) effects of this vitamin are also seen. The effect of different forms of vitamin B6 administration on mice has been shown to decrease signi cantly in Body and adipose tissue weight (21), fasting blood glucose (13,22), liver triglyceride and cholesterol levels and hepatic lipid accumulation (13), fasting insulin levels and increase insulin sensitivity (3,14) in previous studies.…”
mentioning
confidence: 85%
“…Хронічне додаткове вживання піридоксину покращує диференціювання нейробластів у зубчастій звивині та індукує нові зрілі нейрони в гіпокампі [38]. Піридоксин також виявляв нейропротекторну дію в разі експериментального цукрового діабету [39] та при ішемічному пошкодженні мозку [40], зокрема, через гіпокампальні серотонінергічні функції.…”
Section: рисунок 2 утворення серину при дефосфорилюванні фосфосеринуunclassified